Camel gelatin composition, properties, production, and applications - Jaswir, Irwandi; Al-Kahtani, Hassan Abdullah M.; Octavianti, Fitri; Lestari, Widya; Yusof, Nurlina (IGI Global, 2020)
Gelatin is an important protein produced through partial hydrolysis of collagen from animal parts and byproducts such as cartilage, bones, tendons, and hides. The ability of gelatin to form a thermo-reversible gel at normal body temperature and high water content make it an exceptional food ingredient. A good quality gelatin is translucent, brittle, colorless (sometimes slightly yellow), bland in taste, and odorless. Gelatin has been found useful as stabilizer and filler in dairy products and other food industries. Recently, the global gelatin production net over 300,000 metric tons: 46% were from pigskin, 29.4% from bovine hides, 23.1% from bones, and 1.5% from other parts. Although camels have been recognized as source of meat and milk, utilization of camel bones and skins for gelatin production has not been fully explored. This chapter will discuss the processing of camel gelatin extraction.